2020
DOI: 10.1589/jpts.32.288
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Ergon<sup>®</sup> instrument-assisted soft tissue mobilization technique (IASTM), foam rolling, and static stretching application to different parts of the myofascial lateral line on hip joint flexibility

Abstract: This study was aimed to compare the effects of three soft tissue treatments in different parts of the myofascial lateral line (LL) on the hip adduction range of motion (ROM). [Participants and Methods] Thirty university students received Ergon ® instrument-assisted soft tissue mobilization (IASTM) treatment, foam rolling, and static stretching on the upper or lower part of the LL on the side of their non-dominant lower limb, while the other body side served as control. The participants received one treatment p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 14 publications
5
13
0
5
Order By: Relevance
“…The superiority of Ergon IASTM to foam rolling can further be explained by the fact that techniques using narrow-surface equipment are more targeted and can penetrate deeper, thus better mobilizing soft tissue than wider-surface equipment. These positive short-term ROM adaptations after IASTM, and particularly the superiority of such techniques to foam rolling, have also been reported by Simatou et al 7 ) , who found that Ergon IASTM of the lateral myofascial line is more effective in increasing hip adduction ROM than foam rolling and stretching.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The superiority of Ergon IASTM to foam rolling can further be explained by the fact that techniques using narrow-surface equipment are more targeted and can penetrate deeper, thus better mobilizing soft tissue than wider-surface equipment. These positive short-term ROM adaptations after IASTM, and particularly the superiority of such techniques to foam rolling, have also been reported by Simatou et al 7 ) , who found that Ergon IASTM of the lateral myofascial line is more effective in increasing hip adduction ROM than foam rolling and stretching.…”
Section: Discussionsupporting
confidence: 77%
“…However, despite the extensive use of these techniques by sports therapists, their effectiveness has not yet been clarified due to conflicting research findings. Some studies have reported that IASTM and foam rolling can increase range of motion (ROM) and improve athletes’functionality 7 , 8 , 9 , 10 , 11 ) and that athletic elastic taping can support the shoulder joint, thereby increasing its functional efficiency 11 ) . Other studies, however, do not support these findings 12 , 13 ) .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the significant short-term improvement in joint ROM observed in this study supports the conclusions of two systematic reviews 5,6) showing that IASTM can improve patient functionality and significantly increase joint ROM immediately after application. Another recent study found that this improvement can be maintained even for a week 4) .…”
Section: Discussionmentioning
confidence: 88%
“…Given the functional importance of the myofascial lines, we previously conducted two randomized control studies to evaluate the effect of the Ergon ® instrument-assisted softtissue mobilization (IASTM) technique (Ergon ® IASTM Technique, Athens, Greece) in distant and local points of the SBL and LL to evaluate and compare the effects of remote treatment on myofascial elasticity 3,4) .These studies showed that Ergon IASTM treatment of either the upper or the lower part of the SBL and the LL may lead to a significant increase in hamstring and hip adductor flexibility, respectively. Both studies 3,4) also demonstated that applying IASTM techniques to distant points of the myofascial lines led to the same improvement in the elasticity of some areas as that achieved by local treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Participants in Group A received soft tissue techniques in the form of the ERGON IASTM technique [15] in targeted cervical and thoracic spine areas with the aim of the myofascial release of shortened structures. Participants in Group B, for the same purpose, received a classical massage in the same area.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%